Educational Intervention Effects on Depression and Anxiety in Patients after Myocardial Infarction: A Randomized Controlled Trial - Lazzat M. Zhamaliyeva; Damira G. Zhamankulova; Nurgul A. Abenova; Gulbakit K. Koshmaganbetova (Journal of Cardiovascular Development and Disease, 2023)
Depression and anxiety in cardiovascular disease worsen the prognosis of patients. Treatments for these disorders often provide limited improvement. The present study aimed to test, for the first time, the impact of educational technology on anxiety and depressive symptoms in patients participating in a cardiac rehabilitation program. A 12-month randomized controlled trial was conducted, in which 207 patients were randomly assigned to either the experimental (n = 76) or control (n = 69) groups. The intervention involved a structured patient education program provided by medical students who had undergone specially designed training in cardiac rehabilitation. The primary outcomes were death, hospitalization, heart failure, and recurrent myocardial infarction. The study also assessed anxiety and depression. A year later, the experimental group showed a statistically significant decrease in anxiety and depression on the HADS scale, with reductions of 2.0 and 1.9 points, respectively (p < 0.05). The control group showed reductions of 1.5 and 1.2 points (p < 0.05). The difference in the Hamilton Rating Scale for Depression between the groups at 12 months was −1.29 in favor of the main group (95% CI, −0.7 to −1.88), and the standardized mean difference was 0.36 (95% CI, 0.03 to 0.69). No treatment-related adverse events were observed. The results suggest that educational interventions can have a positive impact on mental health. The study’s strengths include a structured intervention, randomization, and long-term follow-up. The limitations include the lack of blinding of study participants and a relatively small sample size.